Reflection on Translation Talent Training in Local Higher Education upon Chinese Culture “Going Global” - Liu, Zhihong (Journal of Theory and Practice in Linguistics, 2025)
Upon the strategy of Chinese culture “going global”, translating should have a dominant role in the info-flow export of Chinese culture because China is growing strong and the world say is of desperate necessity. In large sense the spread of Chinese culture can be reached by qualified translators with adequate Chinese cultural competence, correspondingly how talent training is carried out with distinct characteristics in local higher education by stressing the integration of Chinese culture into their programs. Based on the national standards and the teaching guide by the Ministry of Education, students’ humanistic literacy should be reinforced to develop undergraduate translation major into diversifying modes aiming at cultivating translation talents with strong cultural competence. It is an important path to integrate Chinese culture education into the translation talents training for high quality and specialization in local higher education in order to demonstrate the local distinctiveness and the nationwide talent training diversity. And it is particularly crucial to focus on the local culture integration. Therefore, the talent cultivation program should be improved with school curriculum draft, emphasis on local culture exploration and related school-based textbooks as well as faculty readiness; students must develop their interest field with firm confidence in Chinese culture to grow into high-quality translation talents holding the harmony spirit of Chinese culture for the ultimate purpose of spreading Chinese culture.